Hot Extrusion Effect on the Microstructure and Mechanical Properties of a Mg–Y–Nd–Zr Alloy - Sheng, L.Y.; Du, B.N.; Wang, B.J.; Xu, D.K.; Lai, C.; Gao, Y.; Xi, T.F. (Проблемы прочности, 2018)
A Mg–Y–Nd–Zr alloy was prepared by casting and hot extrusion. The microstructure and mechanical properties of OM, SEM, XRD, TEM, and tensile tests were investigated with casting and hot extruded alloys. The results demonstrate that in a casting Mg–Y–Nd–Zr alloy, the α-Mg matrix is separated into the cell structure by a discontinuously distributed coarse Mg₂₄Y₅/α-Mg eutectic structure and fine Mg₁₂Nd particles.